Sujeito em jogo: o funcionamento do discurso sobre o jogo no Twitch - Sousa, Igor Ramady Lira de (2019)
This Thesis is based on the theoretical assumptions of Discourse Analysis of French tradition, according to the works developed by Michel Pêcheux. The theme of this work involves when the subject that plays starts talking about the game on the website Twitch.tv. We discuss the formulation and circulation of statements about the game initially describing the production of the statement "how to play" of the Manuals and Magazines of a given period. This paper tries to understand if the "how to play" is still possible in the current conjuncture. As a result of the analyzes there was an understanding of an effect produced in the subject that makes the Twitch transmissions. At first, developing the notion of "subject" in Pêcheux (2009), it is described how the subject who plays pass to the position of the "subject-streamer", through the notion of "market subject" of Ferrari and Neckel (2017). It discusses the mode of operation of the production of the transmissions of the platform Twitch.tv characterized as the "uberization", as a form of precarious work. So the subject's constitution on Twitch.tv involves understanding a "mundialized" Market context, along with the crisis of global political representation. Based on Mariani's notion of "discourse about" (1998), it is intended to describe/interpret the mode of formulation of the subject in the transmissions of Twitch.tv. Developing the notion of "metagame", understood through the discursive processes of paraphrase and polysemy through the reading of Orlandi ([1999] 2009), questioning the mobilization of a memory in the production of the senses on the game. In the analysis of two Twitch.tv transmissions, the mode of formulation and circulation on the internet is observed, amid the notion of "reversibility" by Orlandi (1987) and “live” by Gallo (2011a). The algorithms that organize the visualization of the Twitch.tv transmissions for the website user are discussed. This was supported by Oliveira's (2015) spatialisation thesis. The analysis movement produces an understanding of what would be the exchange of position with the "viewer" in the "subject-audience effect" that affects the subject-streamer.